Penerapan HACCP dan Nilai Gizi pada Menu Appetizer Tuna Pasta Salad di PT. Aerofood Indonesia Unit Denpasar (International Forum of Researchers and Lecturers, 2024)
The food industry not only pays attention to aspects of nutritional value and benefits, but also aspects of food safety by implementing a prevention system at the critical point of danger, namely HACCP. PT. Aerofood Indonesia is committed to meeting food needs on board aircraft and plays an active role as a provider of supporting services for Garuda Indonesia airline as the parent company and several foreign airlines. This research was conducted with a focus on the Tuna Pasta Salad menu. The food processing process from receiving raw materials to serving is analyzed according to HACCP principles, while the nutritional content of the menu is evaluated to ensure that the meal is balanced and adequate for passengers during the flight. This research is expected to provide a comprehensive picture of the importance of implementing food safety and nutritional analysis in the inflight catering industry. This research method uses a qualitative approach by conducting observations and interviews. At each stage, food safety at ACS Denpasar is carried out through the application of HACCP. From the results of microbiology laboratory tests, no pathogenic bacteria were found. The nutritional value per serving of tuna pasta salad is 113.4kcal, Fat=5,484g, KH=11,694g, Protein=4,242g. This menu is used as an appetizer which is sufficient for 17.65% of energy, of the 30% requirement for a passenger's lunch based on the nutritional adequacy of an adult, namely 2150 kcal.